Effect of Dioctyl Phthalate on Properties of low molecular weight Poly(vinyl chloride)/Acrylonitrile Butadiene rubber blends - Supri, A Ghani; S.A. Mohamed (Universiti Sains Malaysia (USM), 2010)
Organized by School of Materials and Mineral Resources Engineering, University Sains Malaysia (USM), 10th - 11th April 2007 at Penang